Validation of Radiolabeling of Drug Formulations for Aerosol Deposition Assessment of Orally Inhaled Products - Devadason, Sunalene G.; Chan, Hak-Kim; Haeussermann, Sabine; Kietzig, Claudius; Kuehl, Philip J.; Newman, Stephen; Sommerer, Knut; Taylor, Glyn (Journal of aerosol medicine, 2012)
Radiolabeling of inhaler formulations for imaging studies is an indirect method of determining lung deposition and regional distribution of drug in human subjects. Hence, ensuring that the radiotracer and drug exhibit similar aerodynamic characteristics when aerosolized, and that addition of the radiotracer has not significantly altered the characteristics of the formulation, are critical steps in the development of a radiolabeling method. The validation phase should occur during development of the radiolabeling method, prior to commencement of in vivo studies. The validation process involves characterization of the aerodynamic particle size distribution (APSD) of drug in the reference formulation, and of both drug and radiotracer in the radiolabeled formulation, using multistage cascade impaction. We propose the adoption of acceptance criteria similar to those recommended by the EMA and ISAM/IPAC-RS for determination of therapeutic equivalence of orally inhaled products: (a) if only total lung deposition is being quantified, the fine particle fraction ratio of both radiolabeled drug and radiotracer to that of the reference drug should fall between 0.85 and 1.18, and (b) if regional lung deposition (e.g., outer and inner lung regions) is to be quantified, the ratio of both radiolabeled drug and radiotracer to reference drug on each impactor stage or group of stages should fall between 0.85 and 1.18. If impactor stages are grouped together, at least four separate groups should be provided. In addition, while conducting in vivo studies, measurement of the APSD of the inhaler used on each study day is recommended to check its suitability for use in man.